Majelis Taklim dan Perannya dalam Meningkatkan Kesadaran Beragama - Muhammad Yunus (Jurnal Budi Pekerti Agama Islam, 2024)
This article describes the role of majelis taklim in increasing religious awareness. This taklim assembly is a place to train religious awareness. This research is a qualitative type using observation and interview data collection techniques. The findings of this study are that Nurul Ihsan taklim assembly plays an active role in providing religious education to members and the surrounding community. Through activities such as recitation, Quranic studies, and fiqh studies, the taklim assembly provides a deep understanding of Islamic teachings and instills religious values. This contributes to increasing people's religious awareness, both in the aspects of faith, worship, and morals.